Methodological Considerations for Advancing Research on the Health and Wellbeing of Sexual and Gender Minority Youth - Schrager, Sheree M; Steiner, Riley J; Bouris, Alida M; Macapagal, Kathryn; Brown, C Hendricks (LGBT health, 2019)
Continued research with sexual and gender minority (SGM) youth is essential both to understand health disparities and to develop interventions targeting those disparities, but conducting rigorous, ethical research with these populations remains a substantial challenge. In addition to considerations for research with adolescents in general, such as utilizing developmentally appropriate measures and obtaining parental permission, factors unique to SGM youth must be addressed at every step of the research process. Defining the study population is complex, as is recruiting a sample once it is defined. Measurement is another challenge, given the paucity of measures developed for or validated with SGM samples. Key constructs, such as sexual orientation, gender identity, and family acceptance, are not amenable to randomization and involving minor participants' parents poses ethical concerns given the precarious home and safety situations that can arise from employing typical study procedures with youth who have a stigmatized identity. In this article, we examine some of these unique methodological challenges. Informed by theoretical and empirical literature, practical experience, and an ongoing dialogue with SGM youth themselves, we present a guide to best practices for ethical, productive research with SGM youth. By discussing existing approaches to studying SGM youth and suggesting innovative ways to approach the questions that remain, we hope to assist the research community in addressing methodological gaps to advance research on SGM youth in relation to families and schools.